The Nevanlinna parametrization for a matrix moment problem - Lopez-Rodriguez, Pedro (Mathematica Scandinavica, 2001)
We obtain the Nevanlinna parametrization for an indeterminate matrix moment problem, giving a homeomorphism between the set V of solutions to the matrix moment problem and the set V of analytic matrix functions in the upper half plane such that V(λ )^*V(λ )I. We characterize the N-extremal matrices of measures (those for which the space of matrix polynomials is dense in their L^2-space) as those whose corresponding matrix function V(λ ) is a constant unitary matrix.